To the chief editor of the journal "Endodontics Today" professor Mitronin A.V. - article Editorial (LLC "Endo Press", 2021)
I congratulate you and all the staff of the editorial staff of the journal on the 20th anniversary. The journal "Endodontics Today" is included in the list of peer-reviewed scientific journals and publications of the Higher Attestation Commission of the Ministry of Education and Science of the Russian Federation, in which the main provisions of dissertations for the degree of Doctor and Candidate of Sciences should be published.The journal reflects the state of medical and dental science and practice in Russia and the world in the field of dentistry and the section of therapeutic dentistry - endodontics on the basis of fundamental research of an applied nature. Recommended by the Dental Association of Russia to reflect materials on topical issues of providing dental care to the population.The high scientific and practical potential of the editorial office allows the journal to be in leading positions among the periodicals of journals in the field of dentistry. The pages of the journal continue to be open to dentists, scientific researchers of medical universities in all regions of the Russian Federation, countries of the near and far abroad.President of the Russian Dental AssociationDoctor of Medical Sciences, Professor D.A. Trunin